Implementation of the Joint Business Group (KUBE) Program in Poverty Alleviation in Sumedang District - Willya Achmad (Jurnal Ekonomi, 2022)
Sumedang Regency is one of West Java Province's regencies with a significant number of rising poverty rates that exceed provincial and even national rates. The Joint Business Group (KUBE) strategy is one type of poverty reduction initiative based on community empowerment. Consequently, this study examines the Implementation of the Joint Business Group (KUBE) Program in Poverty Alleviation in the Sumedang Regency, with a particular emphasis on the crucial function of facilitators. This study employs a qualitative, descriptive methodology. The results indicated that KUBE required the role of a companion in addressing poverty by enhancing intellectual talents, social psychology, skills, and levels of community welfare. However, the reality on the ground is that assistants are not backed by proper facilities, necessitating a paradigm shift that focuses on the assistance process, the mentorship process, what they have, their competency, time, facilities, and reports